Maternal Feeding Practices among Children with Feeding Difficulties—Cross-sectional Study in a Brazilian Reference Center - Machado, Rachel H. V.; Tosatti, Abykeyla M.; Malzyner, Gabriela; Maximino, Priscilla; Ramos, Cláudia C.; Bozzini, Ana Beatriz; Ribeiro, Letícia; Fisberg, Mauro (Frontiers in Pediatrics, 2018)
Background Given the positive influence of responsive caregiving on dietary habits in childhood, to raise awareness of caregivers regarding their behavior is crucial in multidisciplinary care on infant feeding. Objectives To identify the most common responsive and non-responsive feeding practices in mothers of children with feeding complaints, as well as to seek associations between practices and caregivers’ profile. Methods Cross-sectional study with 77 children under 18 years old, with complaints of feeding difficulties. Data were collected during interviews with mothers: child age, gender, duration of exclusive breastfeeding, presence of organic disease, dynamics of bottle use, self-feeding practices and posture at meals, use of appropriate feeding equipment; basic information about the mothers (parity and level of education), caregiver feeding style, presence of coercive feeding, frequency and characteristics of family meals. Statistical analysis considered significance level at 5%. Results The non-responsive profile predominated among mothers (76.2%, with the Authoritarian style being the most prevalent—39.7%). The responsive profile was characterized by absence of coercive feeding, stimulation of self-feeding practices, use of appropriate feeding equipment and meal environment, with interaction at meals. Non-responsive profile consisted of both inadequate environment and posture at meals, use of distraction and coercive feeding, lack of shared meals, and disregard for children’s hunger signals. Only the habit of sharing meals with children was associated with mothers’ profile, and considered a protection factor against non-responsive care (OR 0.23; 95% CI 0.06–0.88). Both Authoritarian (p = 0.000) and indulgent mothers (p = 0.007) breastfed exclusively for longer time than negligent ones. There was a higher level of interaction with children in “responsive” parental style (OR 0.056; p = 0.01) compared to other feeding styles. Conclusion Results highlight the need for educational interventions focused on caregivers’ behaviors.